Analysis Of Room Promotion Activities At Kambaniru Beach Hotel & Resort, East Sumba - Rulli Saragi; Boiris Milyardo; Desandi Sharhaldi Takanjanji (Al-Makki Publisher, 2024)
This research evaluates the impact of room promotions at Kambaniru Beach Hotel & Resort, East Sumba, on increasing competitiveness and occupancy rates. Using a qualitative approach and case study method, the research focuses on five promotion elements: advertising, sales promotion, public relations, direct marketing, and digital marketing. Data was collected through observation, in-depth interviews, literature reviews, and documentation analysis, then analyzed using data reduction, presentation, and conclusion drawing methods, with validation through triangulation. The research results show that using social media and digital platforms for promotions successfully attracts millennial customers, while sales promotions and public relations have a minor impact. The main findings reveal that bundled package offers and seasonal discounts are the most effective promotion strategies, significantly increasing occupancy rates. However, the main challenges are seasonal fluctuations, budget limitations, and a need for more staff training in digital tools. Based on these findings, practical implications include enhancing digital promotions, refining advertising messages, and regularly assessing service quality. This research concludes that integrated and diverse promotion strategies are crucial for consistently increasing hotel occupancy and revenue and strengthening marketing strategies in the competitive hospitality industry.